A long hypoxia-inducible factor 3 isoform 2 is a transcription activator that regulates erythropoietin - Tolonen, Jussi-Pekka; Heikkilä, Minna; Malinen, Marjo; Lee, Hang-Mao; Palvimo, Jorma J.; Wei, Gong-Hong; Myllyharju, Johanna (Cellular and molecular life sciences : CMLS, 2020)
Hypoxia-inducible factor (HIF), an αβ dimer, is the master regulator of oxygen homeostasis with hundreds of hypoxia-inducible target genes. Three HIF isoforms differing in the oxygen-sensitive α subunit exist in vertebrates. While HIF-1 and HIF-2 are known transcription activators, HIF-3 has been considered a negative regulator of the hypoxia response pathway. However, the human HIF3A mRNA is subject to complex alternative splicing. It was recently shown that the long HIF-3α variants can form αβ dimers that possess transactivation capacity. Here, we show that overexpression of the long HIF-3α2 variant induces the expression of a subset of genes, including the erythropoietin ( EPO ) gene, while simultaneous downregulation of all HIF-3α variants by siRNA targeting a shared HIF3A region leads to downregulation of EPO and additional genes. EPO mRNA and protein levels correlated with HIF3A silencing and HIF-3α2 overexpression. Chromatin immunoprecipitation analyses showed that HIF-3α2 binding associated with canonical hypoxia response elements in the promoter regions of EPO . Luciferase reporter assays showed that the identified HIF-3α2 chromatin-binding regions were sufficient to promote transcription by all three HIF-α isoforms. Based on these data, HIF-3α2 is a transcription activator that directly regulates EPO expression.